Exploring Speech Strategies in Directive Speech Acts in Contemporary Indonesian Novels - Rejeki, Winda Putri; Manaf, Ngusman Abdul (Journal of Languages and Language Teaching, 2025)
One prominent type of speech act found in communication and literary texts is the commanding speech act. This type of speech act consists of utterances that express commands, often characterized by imperative sentence structures. Commanding speech acts are commonly found in prose literary works, including novels. Therefore, this study aims to analyze speech act strategies in contemporary novels with themes of urban adolescent life, focusing on the distribution of speech act types, the relationship between the speaker and listener, and the pragmatic functions of the utterances. The study applied a qualitative study using observation and note-taking techniques to analyze dialogue data from the novels' characters. Data were collected from three novels: Hanna, Transit, and Malioboro at Midnight. The analysis results show that direct, no-nonsense strategies are the most dominant type, followed by direct strategies with positive politeness and direct strategies with negative politeness. Indirect or ambiguous strategies are rarely used, while internal monologue strategies are not found. The choice of speech act strategies is influenced by relational closeness and social hierarchy, with the context of equal status and familiarity being predominant. Speech act strategies support the narrative by strengthening character relationships, creating tension, or introducing humor, ultimately enriching the reader's experience in understanding the conflicts and dynamics of the characters' interactions. This research contributes to pragmatic studies, particularly in understanding speech act strategies in contemporary literary works.